SUSTAINABLE PARTNERSHIP FOR FLORICULTURE START-UP - Nyayu Lathifah Tirdasari; Salma Mutmainah; Idqan Fahmi (Journal of Islamic, Social, Economics and Development, 2022)
A partnership is one of the essential aspects of business, a prominent venture, and a small enterprise. However, creating a sustainable partnership needs many requirements and a good relationship between business and partners. These paper objectives divided into three purposes. First, to identify the characteristics of partners. Second, to examine the existing partnership. Third, to determine the sustainable partnership strategy. This research employed the case study method. This study used a descriptive method by utilizing observation, interviews, and questionnaires to collect the data. This study examines a start-up in Indonesia that focuses on providing floriculture services, such as landscape design, garden consultation, and many more. In Indonesia, the business of floriculture is experiencing a significant increase. It is evidenced by the high demand for ornamental plants, which is getting higher every year. The result indicates that the existing partnership performed less optimal in achieving the interests of the partnership. Partners' characteristics are identified from several aspects, including gender, age, education level, gardening experience, and partnership length. Most of the partner who was respondents were male. From the age aspect, most partners belong to the productive age group. This age increases work productivity in line with their physical abilities, compared to non-productive age workers. IPA analysis carried out based on two categories, namely the business and the partner. The two categories revealed different results. The difference perceptions considering the obstacles are due to different main objectives in implementing each party's partnership. To fulfil the partnership improvement, having the same viewpoint and agreement in running the partnership is necessary. This paper formulates a plan for the partnership improvement, such as to create operational standardization, to coach the partners, to make a garden nursery, and to create an integrated operational system.